2012
DOI: 10.4067/s0717-65382012000300006
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal changes in oocyte development, growth and population size distribution of Percilia gillissiand Trichomycterus areolatus in the Itata basin, Chile

Abstract: Seasonal changes in oocyte development, growth and population size distribution of Percilia gillissi and Trichomycterus areolatus in the Itata basin, ChileCambio estacionales en el desarrollo de oocitos, crecimiento y distribución de talla poblacional de Percilia gillissi y Trichomycterus areolatus en la cuenca del río Itata, Chile GUSTAVO ABSTRACTThere is scarce basic biological data on native freshwater fi sh species from Chile and next to zero on growth, gonad development and reproduction, which are crit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Information concerning the biology and behavior of both species is incompletely known. There are a few reports about the reproduction and behavior of Percilia gillisi (Kilian, Campos, 1969;Chiang et al, 2011;Chiang et al, 2012) and ontogenetic changes of P. irwini (Aedo, Habit, 2009). There is concern about the present situation of the two species, which are currently catalogued as threatened in Chile.…”
Section: E180102[11]mentioning
confidence: 99%
“…Information concerning the biology and behavior of both species is incompletely known. There are a few reports about the reproduction and behavior of Percilia gillisi (Kilian, Campos, 1969;Chiang et al, 2011;Chiang et al, 2012) and ontogenetic changes of P. irwini (Aedo, Habit, 2009). There is concern about the present situation of the two species, which are currently catalogued as threatened in Chile.…”
Section: E180102[11]mentioning
confidence: 99%
“…Bahamonde et al (81) point out that intersex can occur, as we already mentioned, spontaneously in gonochoristic species exposed to EDCs. This fact together with the evidence of Chiang et al (67,80) who did not observe this phenomenon and could determine the size of first sexual maturation for both sexes separately, suggests that the specimens found by Riffo (83) in the "Peuco" stream (southern limit of the province of Santiago, an area of high agricultural use and pesticides with potential ED) are the first evidence of EDCs in Chile.…”
Section: Discussionmentioning
confidence: 81%
“…It is necessary to understand that fish are constantly subjected to environmental stress (21,22) before planning EDC effect studies, including changes in temperature, hypoxia, sediment loads, flow rate, among others. To understand and to have the ability to extrapolate the effects observed in the individual organism with a chemical or mixture of chemicals having endocrine disruptive properties, cellular and physiological seasonal variations associated with changes in metabolic rates and fish reproductive status must be taken into consideration when evaluating the impacts on individuals and populations (9,21,33,(66)(67)(68)(69)(70)(71)(72)(73)(74)(75)(76)(77)(78)80).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is worth noting that much of the movement detected was directional upstream movement, which could support this hypothesis. Furthermore, a study investigating oocyte development of a closely related species ( Percilia gilissi ) found that this species has an extended spawning season, spanning from the middle of austral winter (July) to the start of summer (December) (Chiang et al ., 2012). This period also corresponds to higher flow regime in the region, which could make upstream movement more difficult because of high water velocity, but could also facilitate such movements by improving upstream connectivity, especially in part of the catchment subjected to seasonal drought.…”
Section: Discussionmentioning
confidence: 99%